2013
DOI: 10.1039/c2sc21321d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adsorbed gas at liquid/solid interfaces on heterogeneous cavitation

Abstract: The presence of dissolved gas at the solid/liquid interface can play a crucial role in heterogeneous cavitation. Here we focus our attention on the relationship between gas conditions and cavitation nucleation at planar solid surfaces with alternating hydrophobic/hydrophilic properties. Tapping mode atomic force microscopy and optical microscopy were used to monitor the gas adsorption on the patterns before sonication. Scanning electron microscopy revealed the effects of collapsing cavitation bubbles on the ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 49 publications
3
55
0
Order By: Relevance
“…The effective interfacial slip influenced by effects associating surface morphology such as wettability, solid atomic arrangement, surface roughness and interfacial nanobubbles (INBs) is still under intense investigation [19]. INBs, the gaseous domains formed at a solid-liquid interface, have been shown to exist on hydrophobic as well as hydrophilic substrates [20]. Using atomic force microscopy, Yang et al [21] demonstrated a strong correlation between surface roughness and the concentration of nanobubbles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective interfacial slip influenced by effects associating surface morphology such as wettability, solid atomic arrangement, surface roughness and interfacial nanobubbles (INBs) is still under intense investigation [19]. INBs, the gaseous domains formed at a solid-liquid interface, have been shown to exist on hydrophobic as well as hydrophilic substrates [20]. Using atomic force microscopy, Yang et al [21] demonstrated a strong correlation between surface roughness and the concentration of nanobubbles.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned results demonstrate that effective slip length is strongly influenced by several coupled factors, such as surface roughness, wettability, and the presence of nanobubbles. In addition, properties intrinsic to solids and fluids, such as the atomic arrangement of solids, as well as parameters related to wall-fluid interaction must be taken into account [20]. This study employed molecular dynamics (MD) simulation in a series of investigations aimed at determining the means by which boundary behaviour is influenced by wettability and the presence of INB.…”
Section: Introductionmentioning
confidence: 99%
“…Lubricant contains dissolved gases which accounts for about 10 percent of its volume [1]. The drop in local pressure below saturation pressure, results in release of these dissolved gases from 2 oil, which is termed as gaseous cavitation.…”
Section: Introductionmentioning
confidence: 99%
“…The current techniques include trapping by microcavities, emulsion direct adsorption, microprinting, and others (6). The solvent exchange process is a simple and generic approach for producing droplets or bubbles at solid-liquid interfaces that are only several tens to hundreds of nanometers in height, or a few femtoliters in volume (7)(8)(9)(10)(11). The approach has attractive advantages, such as its capability of producing a large number of nanodroplets in one simple step, and its generality in chemical composition of the droplet liquid, and flexibility in aspect ratio of the droplets and spatial structure or size of the substrate (9,12).…”
mentioning
confidence: 99%